Extracellular tau clearance is governed by its aggregation state and independent of microglial activation by LPS and IFN-γ - Andrew Shultz; Anna Vincze; Todd T. Yau; Emma L. Poirier; Hannah Demanche; Jennifer N. Rauch (Neurobiology of Disease)
Microglia are the tissue resident macrophages of the brain and their contribution to tau pathology progression remains to be fully understood. In this study, we developed a quantitative platform to elucidate the processing of extracellular tau within human induced pluripotent stem cell (iPSC)-derived microglia. We show that iPSC-derived microglia internalize monomeric and fibrillar tau through different cellular mechanisms and with different clearance kinetics. Acute inflammatory activation of microglia alters tau endocytosis, but surprisingly does not impact tau clearance. These results highlight the importance of the microglial endo-lysosome system as a regulator of tau pathology that is decoupled from acute microglial activation.